2007
DOI: 10.1152/ajplung.00009.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β is the primary initiator of pulmonary inflammation following liver injury in mice

Abstract: Hepatic injury can lead to systemic and pulmonary inflammation through activation of NF-κB-dependent pathways and production of various proinflammatory cytokines. The exact mechanism remains unknown, although prior research suggests interleukin-1β (IL-1β) plays an integral role. Cultured murine alveolar macrophages were used to identify an optimized IL-1β-specific short interfering RNA (siRNA) sequence, which then was encapsulated in liposomes and administered intraperitoneally to transgenic HLL mice (5′-HIV-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
(45 reference statements)
1
15
0
Order By: Relevance
“…IL-1β is not a direct chemoattractant for neutrophils, but it mediates neutrophil recruitment through the synthesis of IL-6, ICAM-1, and CXCL-1. 14 We confirmed that IL-1β stimulated the expression of IL-6, ICAM-1, and CXCL-1 in lung-ECs ( Figure 3F-H) and neutrophil adhesion to lung-ECs ( Figure 3I and 3J), both of which were blocked by IL-1R1 antibody-mediated neutralization. The increase in lung IL-6, ICAM-1, CXCL-1 expression after MI was also blocked by IL-1R1 antibody, and IL-1β stimulated lung IL-6, ICAM-1, and CXCL-1 expression in the absence of MI ( Figure 3K-M).…”
Section: Il-1β Mediates Neutrophil Infiltration Into the Alveolar Spasupporting
confidence: 69%
“…IL-1β is not a direct chemoattractant for neutrophils, but it mediates neutrophil recruitment through the synthesis of IL-6, ICAM-1, and CXCL-1. 14 We confirmed that IL-1β stimulated the expression of IL-6, ICAM-1, and CXCL-1 in lung-ECs ( Figure 3F-H) and neutrophil adhesion to lung-ECs ( Figure 3I and 3J), both of which were blocked by IL-1R1 antibody-mediated neutralization. The increase in lung IL-6, ICAM-1, CXCL-1 expression after MI was also blocked by IL-1R1 antibody, and IL-1β stimulated lung IL-6, ICAM-1, and CXCL-1 expression in the absence of MI ( Figure 3K-M).…”
Section: Il-1β Mediates Neutrophil Infiltration Into the Alveolar Spasupporting
confidence: 69%
“…These results suggested that the increased mortality of nonneutropenic mice infected with this mutant is due in part to an overexuberant inflammatory response. To investigate this possibility, we determined the pulmonary fungal burden, as well as pulmonary levels of MPO (a marker of phagocyte accumulation [12,40]) and proinflammatory cytokines, in these mice. After 4 days of infection, the pulmonary galactomannan content of mice infected with the ⌬dvrA mutant was significantly higher than that of mice infected with the wild-type strain (P ϭ 0.018), but not that of mice infected with the ⌬dvrA::dvrA-complemented strain (P ϭ 0.21) (Fig.…”
Section: Vol 9 2010mentioning
confidence: 99%
“…The MPO content was used to assess the accumulation of phagocytes during infection (12,40). The MPO levels in the lung homogenates were measured by enzyme immunoassay (Cell Sciences).…”
mentioning
confidence: 99%
“…This organ is considered one of the main sources of proinflammatory cytokines in chronic systemic inflammation associated with aging and related to chronic age-related diseases (Aravinthan et al, 2014;Glasgow et al, 2007). In the present work, we study the effect of RSV in systemic inflammation as a function of age in mouse liver and assess whether RSV modulates these effects.…”
Section: Introductionmentioning
confidence: 99%
“…In this systemic inflammatory status, the liver has being indicated as playing a central role. This is because, the liver not only contains the greatest concentration of the body's resident tissue macrophages, the Kupffer cells, but hepatocytes can also be a main source of a variety of proinflammatory cytokines (Glasgow et al, 2007).…”
Section: Introductionmentioning
confidence: 99%